Analisa Ukuran Antropometri Pelindung Wajah COVID - 19 Hasil Manufaktur Mesin 3D Printing - Zulfadli; Mahmud; Dirhamsyah, Muhammad; Samsul Bahri; Azwar; Sariyusda (Politeknik Negeri Batam, 2025)
The COVID-19 pandemic has not only resulted in significant loss of life but has also caused a critical shortage of Personal Protective Equipment (PPE) for healthcare workers. In response, the global community has leveraged 3D Printing technology to produce face shields. This study aims to analyze and evaluate the conformity of the dimensions of 3D-printed face shields with the head anthropometric measurements of the Indonesian population. Anthropometric data from three head segments (Head Length/D1, Head Breadth/D2, and Face Height/D3) were collected from 377 subjects. Three face shield models (PW1: low grade, PW2: medium grade, PW3: high grade) were manufactured using a 3D Printing machine. The analysis results indicate that the existing designs are not fully compatible with the percentile dimensions of the Indonesian population. Modifications to the frame and visor dimensions are required to better align with Indonesian anthropometric data. Additionally, adjustments in 3D Printing process parameters and improved product quality are essential to achieve a more ergonomic design.